A conceptual framework on body representations and their relevance for mental disorders - Möllmann, Anne; Heinrichs, Nina; Herwig, Arvid (Frontiers in Psychology, 2024)
Many mental disorders are accompanied by distortions in the way the own body is perceived and represented (e.g., eating disorders, body dysmorphic disorder including muscle dysmorphia, or body integrity dysphoria). We are interested in the way these distortions develop and aim at better understanding their role in mental health across the lifespan. For this purpose, we first propose a conceptual framework of body representation that defines this construct and integrates different perspectives (e.g., cognitive neuroscience, clinical psychology) on body representations. The framework consists of a structural and a process model of body representation emphasizing different goals: the structural model aims to support researchers from different disciplines to structure results from studies and help collectively accumulate knowledge about body representations and their role in mental disorders. The process model is reflecting the dynamics during the information processing of body-related stimuli. It aims to serve as a motor for (experimental) study development on how distorted body representations emerge and might be changed. Second, we use this framework to review the normative development of body representations as well as the development of mental disorders that relate to body representations with the aim to further clarify the potential transdiagnostic role of body representations.